Novel SnO2@open microcell-liked graphene network as efficient detection for NO2. Issue 197 (24th March 2019) - Liu, Xin; Ji, Tianyi; Tian, Menghan; Sun, Jianbo
Abstract: The design of reduced graphene oxide (RGO) with novel porous structure has attracted tremendous attention owing to their larger specific surface area. Herein, three-dimensional open microcells, bowl-shaped RGO were fabricated through spray drying method which employed polystyrene spheres as a sacrificial template. The bowl-shaped, open microcell-liked pores observed in the RGO network had an average diameter of ≈1 μm. Subsequently, the catalytic SnO2 nanoparticles were loaded on RGO network via a simple solvothermal method (SnO2 @RGO), and their gas sensing properties were investigated at room temperature (RT). In a comparison with pristine RGO network, the SnO2 @RGO composite exhibited almost 4 times higher response to 400 ppm NO2 at RT and rapid recovery time. The extraordinary sensing performance can be attributed to the novel open microcell-liked porous microstructure with the SnO2 catalyst nanoparticles.